Integrating Digital Literacy and Entrepreneurship in Pesantren Curriculum for Economic Empowerment - Agung Setiawan (Edu Spectrum: Journal of Multidimensional Education, 2024)
This study explores the integration of digital literacy and entrepreneurship into the curriculum of Islamic boarding schools (pesantren) to promote economic empowerment. Utilizing a qualitative research methodology with a literature review approach, the research examines existing studies, educational models, and theoretical frameworks that support the inclusion of these contemporary skills in pesantren education. The findings highlight the potential benefits of equipping students with digital competencies and entrepreneurial knowledge, which are crucial for achieving economic independence in the digital era. The study identifies best practices and successful case studies from various pesantren that have implemented such curriculum reforms. Additionally, it discusses the challenges and opportunities associated with this educational transformation, including the need for teacher training, curriculum development, and resource allocation. The research concludes that integrating digital literacy and entrepreneurship into pesantren curriculum can significantly enhance the economic prospects of students, thereby contributing to broader socio-economic development. Recommendations for policymakers, educators, and stakeholders are provided to facilitate the effective adoption and implementation of these curricular changes